A new cryoenergy for ventricular tachycardia ablation: a proof-of-concept study. Issue 8 (25th October 2016) - Berte, Benjamin; Sacher, Frédéric; Wielandts, Jean-Yves; Mahida, Saagar; Pillois, Xavier; Weerasooriya, Rukshen; Bernus, Olivier; Jaïs, Pierre
Abstract: Introduction: Lack of transmural lesion formation during radiofrequency (RF) ablation for ventricular tachycardia (VT) is an important determinant of arrhythmia recurrence. The aim of this proof-of-concept study was to evaluate safety and efficacy of a new and more powerful cryoablation system for ventricular ablation. Methods and results: Five healthy female sheep (59 ± 6 kg) underwent a surgical sternotomy for epicardial and endocardial access [endocardial access via right atrial appendage and left ventricular (LV) apex]. A cryoablation system with liquid nitrogen (IceCure) was used to create 3 min freezes at the right ventricle (RV). Left ventricular cryoablation was performed with either a 6 min or 2 × 4 min freezes. To assess safety, ablation was also performed on the mid left anterior descending artery and the proximal coronary sinus. A total of 45 lesions were created (RV epicardial, n = 12; LV epicardial, n = 18; RV endocardial, n = 7; LV endocardial, n = 8; LAD, n = 4; and CS, n = 4). The mean lesion volume was 5055 ± 92 mm 3 (length: 32 ± 4.6 mm, width: 16.0 ± 6.4 mm, and depth: 11.2 ± 4.4 mm). Lesions were transmural in 28/45 (62%) and >10 mm in depth in 35/45 (78%). Of the endocardial lesions, 12/15 were transmural (80%). There was no benefit of the bonus freeze in LV lesions (6 vs. 2 × 4 min: 6790 ± 44 vs. 5595 ± 63 mm 3 ; P = 0.44). All ablated vascular structures appeared macroscopically normal without acute stenosis. One animal died due to incessant Ventricular fibrillation (VF). Conclusion: Our results indicate that a more powerful cryoablation system is able to create large, transmural ventricular lesions from both the endocardium and the epicardium. The technology may hold potential for both surgical and catheter-based VT ablation in humans.